Republic of Mozambique : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Selected Issues paper and Statistical Appendix reviews Mozambique's impressive economic growth, its composition, and its impact on poverty reduction over the past decade. The paper highlights that improvements in total factor productivity, resulting from a stable macroeconomic environment, the implementation of structural reforms, and high inflows of foreign capital and concessional assistance, have been significant. Good progress has been made in reducing poverty and improving social indicators. The paper also takes stock of the tax reform that Mozambique has implemented since 1996.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet